The Representation of Middle Eastern Women in American Cinema: A Case Study of The Stoning of Suraya M. (Film 2008) - خطابي عبير; صحرواي محمد علي (University of Eloued جامعة الوادي, 2025)
تبحث هذه الأطروحة في تمثيل المرأة الشرق أوسطية في السينما الأمريكية، باستخدام فيلم رجم ثريا م. (2008) كدراسة ‏حالة. ومن خلال عدسة نقدية تجمع بين نظرية إدوارد سعيد في الاستشراق ونظرية الفيلم النسوي، تبحث الدراسة ما إذا ‏كان الفيلم يدعم أو يقاوم الصور النمطية التي بناها المستشرقون والتي تسود الثقافة الأمريكية، والتي عادة ما تقدم النساء في ‏الشرق الأوسط كضحايا، بلا صوت، وبدون وكالة. وتسترشد الدراسة بالأسئلة التالية: كيف تم تصوير المرأة الشرق ‏أوسطية في رجم ثريا م. (2008)؟ كيف يؤثر الفيلم على تصورات الجمهور الغربي عن المرأة والثقافة في الشرق ‏الأوسط؟ هل يتحدى الفيلم أو يعزز الصور النمطية عن المرأة في الشرق الأوسط؟ يستكشف البحث أيضًا الطريقة التي ‏يشكل بها الفيلم تصورات المشاهدين الغربيين’ لثقافة الشرق الأوسط والمرأة. ورغم أن الفيلم يسلط الضوء على العنف القائم ‏على النوع الاجتماعي ويعطي صوتا للأنثى المضطهدة، إلا أنه يقع ضمن قواعد السينما الغربية التي قد تؤدي إلى إدامة ‏التمثيل الاستشراقي. إنه يضفي طابعًا شخصيًا على المعاناة ولكنه يفتقر إلى الفروق الثقافية الدقيقة، وغالبًا ما يصور ‏مجتمع الشرق الأوسط على أنه قمعي متجانس. ومع ذلك، فإن الفيلم يرفع أيضًا الوعي الدولي بحقوق المرأة ويثير محادثات ‏حيوية حول العدالة والمقاومة. يتحدى رجم ثريا م. الصور النمطية ويعززها، مما يعكس التوتر في التصوير الغربي لنساء ‏الشرق الأوسط.‏ This dissertation examines the representation of Middle Eastern women in American cinema, using The Stoning of Soraya M. (2008) as a case study. Through a critical lens combining Edward Said’s theory of Orientalism and feminist film theory, the study investigates whether the film supports or resists the Orientalist-constructed stereotypes that are prevalent in American culture, which usually present Middle Eastern women as victims, voiceless, and without agency. The study is guided by the following inquiries: how Middle Eastern women are portrayed in The Stoning of Soraya M.; how the film influences Western audiences' perceptions of Middle Eastern women and culture; and if the film challenges or reinforces stereotypes about Middle Eastern women. The research also explores the way that the film shapes Western viewers’ perceptions of Middle Eastern culture and women. Although the film raises attention to gender violence and provides a voice to an oppressed female, it is situated within Western cinema codes that may perpetuate Orientalist representation. It personalizes suffering yet lacks cultural nuance, often portraying Middle Eastern society as monolithically oppressive. However, the film raises international awareness about women's rights and triggers vital conversations about justice and resistance. The Stoning of Soraya M. both challenges and reinforces stereotypes, reflecting the tension in Western portrayals of Middle Eastern women.
Master's Degree In Literature and Civilization.2025
Keywords: السينما الأمريكية، قمع النساء، نساء الشرق الأوسط، تمثيل، ثريا م.، الصور النمطية.‏; American Cinema; Female Oppression; Middle Eastern Women; Representation; Soraya M.; Stereotypes.